The impact of different determination of intangible fixed assets in accordance with CAS and IPSAS on financial statements - Martin Dvořák; Lukáš Poutník (European Financial and Accounting Journal, 2017)
The paper deals with the determination of intangible assets of Czech public sector. On 15 January 2013, the International Public Sector Accounting Standards Board issued new standard IPSAS 31 - Intangible assets. This standard represents a very sophisticated construction of accounting axioms moving public sector much closer to the private sector. The aim of this paper is to identify and make subsequent comparison of methodological elements in the context of intangible assets according to CAS and IPSAS 31. Moreover the paper tries to show the share of intangible fixed assets to the total assets throughout every type of organization of public sector like regions, municipalities, government departments etc. to assess subsequently the extent of possible impacts on financial situation in case of transition of financial reporting to IPSAS.
Keywords: C10; H50; M41; 650; CAS; Intangible fixed assets; IPSAS